Cohesive zone model of asphalt-aggregate interface under compression and shear. Issue 7 (3rd May 2023) - Guo, Liming; Pan, Ling; Lv, Zhitian; Chen, Yunhui
ABSTRACT: As one of the important indicators of the pavement performance of asphalt, the adhesion performance of asphalt-aggregate has an important impact on the durability of the road. The adhesion mechanism of an asphalt-aggregate interface is studied by molecular dynamics simulation. A shear system model for asphalt is constructed, confined to two aggregates, and the shear simulation is performed at different pressures, temperatures, and shear velocities. The relationship between stress and displacement is investigated. According to the changes in the asphalt model for the shear process, the form of the failure and the failure mechanism of the interface can be analyzed under different conditions. Results show that the asphalt near the asphalt-aggregate interface has obvious signs of stratification along a direction parallel to the interface during the process of applying pressure, the greater pressure applied, the greater speed variation rate between the asphalt and the aggregate. The shear strength limit has a linear relationship with pressure and temperature and a nonlinear relationship with velocity. The cohesion zone mathematical model and its series parameter values suitable for larger-scale numerical analysis are obtained by fitting the curve for the stress displacement of the shear process.